Sanitation and diarrhoea in infancy and CRP level at 18 years: the birth-to-twenty plus cohort - Rihlat Said-Mohamed; Aryeh D. Stein; John M. Pettifor; Shane A. Norris (Taylor & Francis Group, 2019)
Background: Cardiometabolic disease is associated with chronic low-grade inflammation. While low birthweight, childhood stunting and rapid weight gain predict higher adult high-sensitivity C-reactive protein (hs-CRP) concentrations, associations between childhood infections and adulthood CRP are inconsistent. Aim: To assess the associations between sanitation, diarrhoea and a combined score of both from birth to age 2 years and hs-CRP at age 18 years, independently of early life nutrition and adult adiposity. Subjects and methods: This study collected data on sanitation and diarrhoea episodes from birth to 2 years on 756 participants of the Birth-to-Twenty Plus cohort, a birth cohort initiated in South Africa in 1990, and calculated a combined score of both variables. Anthropometry was measured at 2 years and 18 years and hs-CRP at 18 years. Results: Of the participants, 29.5% had no access to indoor flush sanitation and 38.2% experienced ≥1 diarrhoea episode between birth and 2 years. Not having access to indoor flush sanitation and experiencing ≥1 diarrhoea episodes were associated with 1.50 mg/L and 1.52 mg/L higher hs-CRP, respectively. Prevalence of both burdens in infancy was associated with a 2.18 mg/L higher hs-CRP. Conclusion: In this population, poor sanitation and diarrhoea in early life predict elevated CRP in young adulthood, independently of early life nutrition and adiposity.